A hierarchical observer for a non-linear uncertain CSTR model of biochemical processes - Czyżniewski, Mateusz; Łangowski, Rafał (Zielona Góra: Uniwersytet Zielonogórski)
The problem of estimation of unmeasured state variables and unknown reaction kinetic functions for selected biochemical processes modelled as a continuous stirred tank reactor is addressed in this paper. In particular, a new hierarchical (sequential) state observer is derived to generate stable and robust estimates of the state variables and kinetic functions. The developed hierarchical observer uses an adjusted asymptotic observer and an adopted super-twisting sliding mode observer.
Keywords: bioreactors; hierarchical observers; non-linear uncertain systems; observers; state estimation